Victorians - Roberts, Ian.; Moses, Brian (Hoboken : Taylor and Francis, 2012)
This book will support children as they:* Write a school report for a Victorian pupil* Compile the biography of a real-life circus performer- "The Human Canon Ball"* Produce a letter to complain about the after-effects of the Victorian remedy carbolic smoke balls!
Words of wisdomA pleasant stay?; Disasters; Part 2 Anthology; Dotheboys Hall; A Victorian school; Rules . ..; Blessings; Victorian school rhymes; Eton beating; Etiquette rhymes; Miscellaneous rhymes; How to write a letter; The little chimney sweep; Our Mutual Friend; Many happy hours; Victorian street rhymes; The Grace Darling Song; Queen Victoria to Miss Florence Nightingale; The Charge of the Light Brigade; The Tay Bridge Disaster; Notes on anthology selections
Description based upon print version of record.
Keywords: Great Britain - History - Victoria, 1837-1901 - Study and teaching (Elementary) - Great Britain; Education; Great Britain -- History -- Victoria, 1837-1901 -- Study and teaching (Elementary) -- Great Britain; EDUCATION / Teaching Methods & Materials / Social Science; Electronic books